Lithium ion battery and method of manufacturing the same

CN116779947BActive Publication Date: 2026-10-23SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310792012.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2026-10-23
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

但传统的干法工艺中,在进行卷对卷生产制备时对电极膜的强度要求较高,否则很容易导致断带,使得生产速度降低,无法提高生产效率

Benefits of technology

[0020]本申请的锂离子电池的正极活性物质层和/或负极活性物质层在远离正极/负极集流体的一侧表面上复合有多孔纤维膜,电解液能够进入到多孔纤维膜中,并在多孔纤维结构的三维连续孔道作用下,形成连续的锂离子通道,提高了锂离子的快速传递能力。另一方面,多孔纤维膜能够为正负极极片提供支撑和连接作用,在保证循环容量保持率的同时,提升了极片的抗断裂能力,防止在卷对卷生产制备时发生断带,防止极片表面开裂影响电池的性能,提高了生产效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116779947B_ABST
    Figure CN116779947B_ABST
Patent Text Reader

Abstract

The application provides a lithium ion battery and a preparation method thereof. The lithium ion battery comprises a positive electrode, a diaphragm, an electrolyte and a negative electrode. The positive electrode comprises a positive electrode active material layer and a positive electrode current collector. The negative electrode comprises a negative electrode active material layer and a negative electrode current collector. The positive electrode active material layer and / or the negative electrode active material layer is provided with a porous fiber membrane on the side far from the positive / negative electrode current collector. The electrolyte is dispersed in the porous fiber membrane to form a continuous lithium ion channel. The breaking resistance of the electrode sheet is improved, the strip breakage is prevented during the roll-to-roll production and preparation, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion battery technology, and in particular to a lithium-ion battery and its preparation method. Background Technology

[0002] With the rapid development of new energy technologies, lithium-ion batteries are widely used in new energy vehicles and portable electronic devices. However, traditional wet electrode fabrication processes, despite technological advancements, have shown limitations, hindering the industrialization of lithium-ion batteries. In wet processes, the electrode slurry mixing process requires a large amount of NMP (N-methylpyrrolidone). NMP volatilizes during drying, necessitating the establishment of a recycling system to prevent environmental pollution. Furthermore, some organic solvents, such as NMP, are highly hygroscopic, leading to excessively high moisture content during battery fabrication. This can cause problems such as battery swelling and rapid performance degradation during long-term cycling.

[0003] The dry electrode fabrication process contains no solvents, eliminating side reactions caused by solvent residues during lithium-ion battery charging and discharging, and also eliminating safety hazards. However, in traditional dry processes, the strength of the electrode film is required to be high during roll-to-roll production; otherwise, tape breakage can easily occur, reducing production speed and hindering efficiency. Summary of the Invention

[0004] Based on this, it is necessary to provide a lithium-ion battery and its preparation method, wherein the positive electrode active material layer and / or negative electrode active material layer in the lithium-ion battery form a porous fiber membrane on the side away from the positive / negative electrode current collector, and the electrolyte is dispersed in the porous fiber membrane to form a continuous lithium-ion channel; at the same time, it improves the fracture resistance of the electrode sheet, prevents the strip from breaking during roll-to-roll production, and improves production efficiency.

[0005] A first aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, a separator spaced between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode includes a positive electrode active material layer and a positive electrode current collector; the negative electrode includes a negative electrode active material layer and a negative electrode current collector; a porous fiber membrane is formed on the side of the positive electrode active material layer and / or the negative electrode active material layer away from the positive electrode / negative electrode current collector, and the electrolyte is dispersed in the porous fiber membrane to form a continuous lithium-ion channel.

[0006] In some embodiments, the positive electrode active material layer and / or the negative electrode active material layer comprises a fibrous mixture, which includes positive / negative electrode active materials, conductive agents, and binders.

[0007] In some embodiments, the fibrous treatment method includes any one or a combination of two of air jet milling, high-speed mixing, mechanical fusion, or twin-screw extrusion. In some embodiments, the average pore size of the porous fiber membrane is 0.5 μm or more, preferably, the average pore size of the porous fiber membrane is 1 μm or more.

[0008] In some embodiments, the thickness of the porous fiber membrane is less than 12 μm.

[0009] In some embodiments, the porous fiber membrane is made of one or more of polymeric materials, carbon materials, metallic materials, or ceramic materials.

[0010] In some embodiments, the porous fiber membrane is made of one or more of the following materials: polyvinylidene fluoride, polymethyl methacrylate, polyimide, polyetherimide, polycarbonate, polyaramid, cellulose, polyetheretherketone, and perfluorosulfonate ether.

[0011] In some embodiments, the active material is a positive electrode active material or a negative electrode active material, wherein the positive electrode active material includes LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn2O4, LiTi5O 12 Li(Ni) 0.5 Mn 1.5 One or more of O4, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and LiNbO3; the negative electrode active material includes one or more of graphite, silicon, silicon-graphene, silicon-aluminum alloy, tin-based materials, graphene, pitch carbon microspheres, activated carbon, carbon fiber, graphene and carbon nanotubes.

[0012] The second aspect of this application provides a method for preparing a lithium-ion battery, comprising the following steps:

[0013] S1: Dry mixing of positive electrode active material, conductive agent, and binder to prepare positive electrode mixture; dry mixing of negative electrode active material, conductive agent, and binder to prepare negative electrode mixture;

[0014] S2: The positive electrode mixture prepared in S1 is subjected to fibrous treatment to prepare a fibrous positive electrode mixture; the negative electrode mixture prepared in S1 is subjected to fibrous treatment to prepare a fibrous negative electrode mixture.

[0015] S3: Roll pressing is performed on the fibrous cathode mixture prepared in S2 to prepare the cathode active material layer;

[0016] The fibrous negative electrode mixture prepared by S2 is subjected to roll pressing to prepare the negative electrode active material layer;

[0017] S4: By roll pressing, a porous fiber membrane is laminated onto one side surface of the positive electrode active material layer prepared in S3 to prepare a composite positive electrode membrane; by roll pressing, a porous fiber membrane is laminated onto one side surface of the negative electrode active material layer prepared in S3 to prepare a composite negative electrode membrane.

[0018] S5: By rolling, the side surface of the composite positive electrode film prepared in S4 that is not combined with the porous fiber membrane is combined with the positive current collector to prepare a composite positive electrode sheet; by rolling, the side surface of the composite negative electrode film prepared in S4 that is not combined with the porous fiber membrane is combined with the negative current collector to prepare a composite negative electrode sheet.

[0019] S6: The composite positive electrode, composite negative electrode, and separator prepared in S5 are wound or stacked to form a battery cell; or the composite positive electrode, non-composite negative electrode, and separator are wound or stacked to form a battery cell; or the non-composite positive electrode, composite negative electrode, and separator are wound or stacked to form a battery cell; electrolyte is injected into the battery cell, and lithium-ion batteries are prepared through vacuum sealing, standing, formation and other processes.

[0020] The lithium-ion battery of this application has a porous fiber membrane laminated on the surface of the positive and / or negative active material layers away from the positive / negative current collector. The electrolyte can enter the porous fiber membrane, and under the action of the three-dimensional continuous channels of the porous fiber structure, a continuous lithium-ion channel is formed, improving the rapid lithium-ion transport capability. On the other hand, the porous fiber membrane can provide support and connection for the positive and negative electrode sheets, ensuring cycle capacity retention while improving the breakage resistance of the electrode sheets, preventing tape breakage during roll-to-roll production, preventing surface cracking of the electrode sheets from affecting battery performance, and improving production efficiency. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0022] Figure 1 This is a schematic diagram of the structure of the composite positive electrode sheet in one embodiment of this application.

[0023] Figure 2 This is a schematic diagram of the structure of a lithium-ion battery in one embodiment of this application.

[0024] Explanation of reference numerals in the attached figures

[0025] 1. Positive electrode active material layer; 2. Negative electrode active material layer; 3. Positive electrode current collector; 4. Negative electrode current collector; 5. Composite positive electrode sheet; 6. Composite negative electrode sheet; 7. Porous fiber membrane; 8. Separator. Detailed Implementation

[0026] The technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art are within the scope of protection of this application.

[0027] A first aspect of this application provides a lithium-ion battery, including a positive electrode, a negative electrode, a separator spaced between the positive and negative electrodes, and an electrolyte. The positive electrode includes a positive active material layer and a positive current collector; the negative electrode includes a negative active material layer and a negative current collector; a porous fiber membrane is formed on the side of the positive and / or negative active material layers away from the positive / negative current collector. Utilizing the porous structure of the porous fiber membrane, the electrolyte is dispersed in the porous fiber membrane, enhancing the wetting ability of the electrolyte and realizing a through-hole lithium-ion channel.

[0028] In some embodiments, the active material layer forms a porous fiber membrane on the side away from the positive / negative current collector. The porous fiber membrane can provide support and connection for the positive and negative electrode sheets, improve the breakage resistance of the electrode sheets, prevent tape breakage during roll-to-roll production, and improve production efficiency.

[0029] Preferably, the positive electrode active material layer comprises a mixture that has undergone positive electrode fiberization treatment.

[0030] Preferably, the mixture for positive electrode fiberization treatment includes a positive electrode active material, a conductive agent, and a binder.

[0031] Preferably, the negative electrode active material layer comprises a mixture that has undergone negative electrode fiberization treatment.

[0032] Preferably, the mixture undergoing negative electrode fiberization treatment includes a negative electrode active material, a conductive agent, and a binder.

[0033] In some embodiments, the specific type of positive electrode active material is not particularly limited, as long as it can accept and release lithium ions. The positive electrode active material can be a layered structure material, allowing lithium ions to diffuse in two-dimensional space, or a spinel structure, allowing lithium ions to diffuse in three-dimensional space. Preferably, the positive electrode active material can be selected from lithium transition metal oxides, wherein the lithium transition metal oxides can also be doped with other transition metals, non-transition metals, or non-metals. Specifically, the positive electrode active material is preferably selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium phosphates with an olivine structure.

[0034] In some embodiments, the positive electrode active material includes LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2, LiMn2O4, LiTi5O 12 Li(Ni) 0.5 Mn 1.5 One or more of the following: O4, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and LiNbO3.

[0035] In some embodiments, the negative electrode active material may include at least a carbon-based negative electrode material; more preferably, the carbon-based negative electrode material may be selected from one or more of natural graphite, artificial graphite, soft carbon, hard carbon, mesophase carbon microspheres, nano-carbon, and carbon fiber. In addition to carbon-based negative electrode materials, the negative electrode active material may also include one or more of silicon-based materials, tin-based materials, and lithium titanate. Preferably, the silicon-based material is selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys, and the tin-based material is selected from one or more of elemental tin, tin oxide compounds, tin-carbon composites, and tin alloys.

[0036] In some embodiments, the negative electrode active material includes one or more of graphite, silicon, silicon-graphene, silicon-aluminum alloy, tin-based materials, graphene, pitch carbon microspheres, activated carbon, carbon fiber, graphene, and carbon nanotubes.

[0037] In some embodiments, the conductive agent includes, but is not limited to, carbon-based materials, powdered nickel or other metal particles, or conductive polymers. Carbon-based materials may include, for example, particles of carbon black, graphite, SuperP, acetylene black (such as KETCHENTM black or DENKATM black), carbon fibers and nanotubes, graphene, etc. Examples of conductive polymers include polyaniline, polythiophene, polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene)polysulfonated styrene, etc.

[0038] In some embodiments, the binder includes, but is not limited to, one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), polyoxymethylene (POM), polycarbonate (PC), polyamide (PA), acrylic plastics, other polyolefins and their copolymers, polysulfone, polyphenylene ether (PPO), and carboxymethyl cellulose (CMC). Further, the binder is polytetrafluoroethylene (PTFE) or polyvinylidene fluoride (PVDF).

[0039] In some implementations, the positive electrode current collector is not particularly limited, as long as it is conductive and does not cause chemical changes in the battery. Specifically, copper, stainless steel, aluminum, nickel, titanium, or a metal current collector with a surface treated with carbon or other substances can be used.

[0040] In some embodiments, the shape of the negative electrode current collector includes any one of foil shape, plate shape, or grid shape; further, the negative electrode current collector includes any one of elemental aluminum, copper, nickel, or zinc; optionally, the negative electrode current collector is elemental copper, such as copper foil; further, the negative electrode current collector includes any one of aluminum, copper, nickel, or zinc alloy.

[0041] In some embodiments, to prevent internal short circuits, lithium-ion batteries also require a separator located between the positive and negative electrodes to block electron transport within the battery. The separator in this application is any of various separators used in lithium-ion batteries, comprising a material with low resistance to ion migration in the electrolyte and good electrolyte retention capacity.

[0042] In some embodiments, the diaphragm includes, but is not limited to, one or more of polypropylene, polyethylene, polyvinylidene fluoride, polyimide, and polyacrylonitrile.

[0043] In some embodiments, the porous fiber membrane is made of one or more of polymeric materials, carbon materials, metallic materials, or ceramic materials; preferably, the porous fiber membrane is made of one or more of polyvinylidene fluoride, polymethyl methacrylate, polyimide, polyetherimide, polycarbonate, polyaramid, cellulose, polyetheretherketone, and perfluorosulfonate ether.

[0044] In some embodiments, the average pore size of the porous fiber membrane is 0.5 μm or more, preferably 1 μm or more. The average pore size of the porous fiber membrane is controlled within the above range so that the electrolyte can wet the porous fiber membrane. Optionally, the average pore size of the porous fiber membrane is 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.2 μm, 1.4 μm, or 1.6 μm. Preferably, the average pore size is 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, or 2.4 μm, but is not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0045] In some embodiments, the thickness of the porous fiber membrane is 12 μm or less. Controlling the thickness of the porous fiber membrane within the aforementioned range allows the electrode membrane to possess both suitable energy density and good flexibility. Optionally, the thickness of the porous fiber membrane can be 8 μm, 9 μm, 10 μm, 11 μm, or 12 μm, but is not limited to the listed values; other unlisted values ​​within the range are also applicable.

[0046] In some embodiments, the electrolyte includes an electrolyte salt and an organic solvent.

[0047] In some embodiments, the organic solvent includes at least one selected from ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethylene carbonate, propylene carbonate, butene carbonate, ethylene sulfite, propylene sulfite, diethyl sulfite, γ-butyrolactone, dimethyl sulfoxide, ethyl acetate, methyl acetate, tetrahydrofuran, dimethylmethane, 2-dimethyltetrahydrofuran, 1,2-dimethylethane, 1,3-dioxolane, and diethylene glycol dimethyl ether.

[0048] In some embodiments, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalateborate, and lithium bis(oxalateborate).

[0049] The second aspect of this application provides a method for preparing a lithium-ion battery, comprising the following steps:

[0050] S1: Dry mixing of positive electrode active material, conductive agent, and binder to prepare positive electrode mixture; dry mixing of negative electrode active material, conductive agent, and binder to prepare negative electrode mixture;

[0051] S2: The positive electrode mixture prepared in S1 is subjected to fibrous treatment to prepare a fibrous positive electrode mixture; the negative electrode mixture prepared in S1 is subjected to fibrous treatment to prepare a fibrous negative electrode mixture.

[0052] S3: The positive electrode fiberized mixture prepared in S3 is subjected to roll pressing to prepare the positive electrode active material layer;

[0053] The negative electrode fiberized mixture prepared by S3 is subjected to roll pressing to prepare the negative electrode active material layer;

[0054] S4: By roll pressing, a porous fiber membrane is laminated onto one side surface of the positive electrode active material layer prepared in S3 to prepare a composite positive electrode membrane; by roll pressing, a porous fiber membrane is laminated onto one side surface of the negative electrode active material layer prepared in S3 to prepare a composite negative electrode membrane.

[0055] S5: By rolling, the side surface of the composite positive electrode film prepared in S4 that is not combined with the porous fiber membrane is combined with the positive current collector to prepare a composite positive electrode sheet; by rolling, the side surface of the composite negative electrode film prepared in S4 that is not combined with the porous fiber membrane is combined with the negative current collector to prepare a composite negative electrode sheet.

[0056] S6: The composite positive electrode, composite negative electrode, and separator prepared in S5 are wound or stacked to form a battery cell; or the composite positive electrode, non-composite negative electrode, and separator are wound or stacked to form a battery cell; or the non-composite positive electrode, composite negative electrode, and separator are wound or stacked to form a battery cell; electrolyte is injected into the battery cell, and lithium-ion batteries are prepared through vacuum sealing, standing, formation and other processes.

[0057] It should be noted that, in this application, "composite positive electrode sheet" and "composite negative electrode sheet" refer to composite electrode sheets prepared using the preparation method provided in the second aspect of this application. "Non-composite positive electrode sheet" and "non-composite negative electrode sheet" refer to electrode sheets conventionally used in traditional battery preparation methods in the art. For example, a "non-composite positive electrode sheet" may be a lithium cobalt oxide positive electrode sheet, and a "non-composite negative electrode sheet" may be a graphite negative electrode sheet.

[0058] In some embodiments, the method for uniformly mixing the positive or negative electrode active material, conductive agent, and binder in step S1 is a dry mixing process that does not use solvents or uses virtually no solvents.

[0059] The lithium-ion battery preparation method in this application does not include or substantially does not use solvents. The fiberized mixture is rolled into an active material layer in solid form. Through further rolling, a porous fiber membrane is formed on the side of the active material layer away from the positive / negative current collector. The final lithium-ion battery does not include or substantially does not contain solvent residues or impurities. Compared with traditional wet process technology, the electrode film preparation method in this application does not require a complex high-temperature, ultra-low vacuum drying and dehydration process, which reduces energy consumption, improves the cycle life of the product, and is simpler, more flexible, more environmentally friendly, and effectively reduces labor and material costs.

[0060] In some embodiments, a fibrous mixture is prepared by fibrous treatment of a mixture including an active material, a conductive agent and a binder, and the fibrous mixture is rolled to prepare an active material layer.

[0061] In some embodiments, the fiberization process includes, but is not limited to, any one or a combination of two of air jet milling, high-speed mixing, mechanical blending, or twin-screw extrusion.

[0062] In some embodiments, the preparation method of the porous fiber membrane is not particularly limited, and commonly used preparation methods in the art, such as electrospinning, can be used.

[0063] The lithium-ion battery preparation method in this application involves fibrous treatment of a positive or negative electrode mixture to prepare a fibrous mixture, followed by rolling to obtain an active material layer. Then, through rolling, a porous fiber membrane is applied to one side of the active material layer to form a composite positive or negative electrode film. By rolling, the other side of the composite electrode film is combined with a current collector to prepare a composite positive / composite negative electrode sheet. The three-dimensional continuous channels of the porous fiber structure form continuous lithium-ion channels, improving the rapid lithium-ion transport capability. Furthermore, the porous fiber membrane provides support and connection for the positive and negative electrode sheets, ensuring cycle capacity retention while improving the breakage resistance of the electrode sheets and preventing tape breakage during roll-to-roll production. It also improves the tensile strength of the electrode sheets, preventing surface cracking that could affect battery performance, effectively solving the forming process problems of dry-process electrodes.

[0064] The implementation scheme of this application will be described in detail below with reference to specific embodiments.

[0065] Example 1.

[0066] Raw material mixing: Lithium cobalt oxide, acetylene black and polytetrafluoroethylene (PTFE) are put into a mixer in a mass ratio of 93:4:3 and mixed evenly by dry method to prepare positive electrode mixture.

[0067] Fiberization treatment: The mixture is fiberized by air jet milling to prepare a fiberized positive electrode mixture.

[0068] Preparation of the positive electrode active material layer: The fibrous positive electrode mixture is rolled to prepare the positive electrode active material layer.

[0069] Preparation of composite positive electrode film: A porous fiber membrane with a thickness of 10 μm and an average pore size of 1.6 μm was selected; the porous fiber membrane was coated on one side of the positive active material layer by roll pressing to prepare a composite positive electrode film.

[0070] Preparation of composite positive electrode sheet: Aluminum foil is covered on one side of the composite positive electrode film that is not composited with porous fiber membrane, and composite is prepared by roll pressing.

[0071] Lithium-ion battery preparation: A composite positive electrode, a graphite negative electrode, and a PP / PE composite separator are wound together to form a cell. Electrolyte is injected into the cell, and the lithium-ion battery is prepared through vacuum sealing, settling, and formation processes.

[0072] Example 2.

[0073] Raw material mixing: Graphite, acetylene black and polytetrafluoroethylene (PTFE) are put into a mixer in a mass ratio of 93:4:3 and mixed evenly by dry method to prepare negative electrode mixture.

[0074] Fiberization treatment: The mixture is subjected to fiberization treatment using an air jet mill to fibromate the negative electrode mixture and prepare a negative electrode fiberized mixture.

[0075] Preparation of the negative electrode active material layer: The negative electrode fibrous mixture is rolled to prepare the negative electrode active material layer.

[0076] Preparation of negative electrode film: A porous fiber membrane with a thickness of 10 μm and an average pore size of 1.3 μm was selected; the porous fiber membrane was coated on one side of the negative electrode active material layer by roll pressing to prepare a composite negative electrode film.

[0077] Preparation of composite negative electrode sheet: Copper foil is covered on one side of the composite negative electrode film that is not composited with porous fiber membrane, and composite is prepared by roll pressing.

[0078] Raw material mixing: Lithium cobalt oxide, acetylene black and polytetrafluoroethylene (PTFE) are put into a mixer in a mass ratio of 93:4:3 and mixed evenly by dry method to prepare positive electrode mixture.

[0079] Fiberization treatment: The mixture is fiberized by air jet milling to prepare a fiberized positive electrode mixture.

[0080] Preparation of the positive electrode active material layer: The fibrous positive electrode mixture is rolled to prepare the positive electrode active material layer.

[0081] Preparation of composite positive electrode film: A porous fiber membrane with a thickness of 10 μm and an average pore size of 1.3 μm was selected; the porous fiber membrane was coated on one side of the positive active material layer by roll pressing to prepare a composite positive electrode film.

[0082] Preparation of composite positive electrode sheet: Aluminum foil is covered on one side of the composite positive electrode film that is not composited with porous fiber membrane, and composite is prepared by roll pressing.

[0083] Preparation of lithium-ion batteries: The composite positive electrode sheet, the composite negative electrode sheet, and the PP / PE composite separator prepared above are wound together to form a cell. Electrolyte is injected into the cell, and lithium-ion batteries are prepared through vacuum sealing, standing, formation and other processes.

[0084] See Figure 1 , Figure 1 This is a schematic diagram of the composite positive electrode 5. The composite positive electrode 5 includes a positive electrode film and a positive current collector 3. The positive electrode film includes a porous fiber membrane 7 and a positive active material layer 1.

[0085] See Figure 2 , Figure 2 This is a schematic diagram of the lithium-ion battery structure in this embodiment. The lithium-ion battery includes a composite positive electrode 5, a composite negative electrode 6, and a separator 8. The composite positive electrode 5 includes a positive electrode film and a positive current collector 3. The positive electrode film includes a porous fiber membrane 7 and a positive active material layer 1. The composite negative electrode 6 includes a negative electrode film and a negative current collector 4. The negative electrode film includes a porous fiber membrane 7 and a negative active material layer 2.

[0086] Example 3.

[0087] This embodiment differs from Embodiment 1 only in the selection of the porous fiber membrane; all other steps are the same, as follows:

[0088] Raw material mixing: Lithium cobalt oxide, acetylene black and polytetrafluoroethylene (PTFE) are put into a mixer at a mass ratio of 93:4:3 and mixed evenly by dry method to prepare positive electrode mixture.

[0089] Fiberization treatment: The positive electrode mixture is subjected to fiberization treatment using an air jet mill to prepare a fiberized positive electrode mixture.

[0090] Preparation of the positive electrode active material layer: The positive electrode fibrous mixture is rolled to prepare a positive electrode fibrous mixture film.

[0091] Preparation of the positive electrode film: A porous fiber membrane with a thickness of 12 μm and an average pore size of 1.0 μm was selected; the porous fiber membrane was coated on one side surface of the positive electrode fiberized mixture film by roll pressing to prepare the positive electrode film.

[0092] Preparation of composite positive electrode sheet: Aluminum foil is covered on one side of the composite positive electrode film that is not composited with porous fiber membrane, and composite is prepared by roll pressing.

[0093] Lithium-ion battery preparation: Composite positive electrode sheet, graphite negative electrode sheet and PP / PE composite separator are wound and stacked to form a cell, electrolyte is injected into the cell, and lithium-ion battery is prepared through vacuum sealing, standing, formation and other processes.

[0094] Example 4.

[0095] This embodiment differs from Embodiment 1 only in the selection of the porous fiber membrane; all other steps are the same, as follows:

[0096] Raw material mixing: Lithium cobalt oxide, acetylene black and polytetrafluoroethylene (PTFE) are put into a mixer at a mass ratio of 93:4:3 and mixed evenly by dry method to prepare positive electrode mixture.

[0097] Fiberization treatment: The positive electrode mixture is subjected to fiberization treatment using an air jet mill to prepare a fiberized positive electrode mixture.

[0098] Preparation of the positive electrode active material layer: The positive electrode fibrous mixture is rolled to prepare a positive electrode fibrous mixture film.

[0099] Preparation of the positive electrode film: A porous fiber membrane with a thickness of 12 μm and an average pore size of 0.5 μm was selected; the porous fiber membrane was coated on one side surface of the positive electrode fiberized mixture film by roll pressing to prepare the positive electrode film.

[0100] Preparation of composite positive electrode sheet: Aluminum foil is covered on one side of the composite positive electrode film that is not composited with porous fiber membrane, and composite is prepared by roll pressing.

[0101] Lithium-ion battery preparation: Composite positive electrode sheet, graphite negative electrode sheet and PP / PE composite separator are wound and stacked to form a cell, electrolyte is injected into the cell, and lithium-ion battery is prepared through vacuum sealing, standing, formation and other processes.

[0102] Comparative Example 1.

[0103] The only difference between this comparative example and Example 1 is that a porous fiber membrane was not used in the preparation method of this comparative example. The specific process is as follows:

[0104] Raw material mixing: Lithium cobalt oxide, acetylene black and polytetrafluoroethylene (PTFE) are put into a high-speed mixer at a mass ratio of 93:4:3 and mixed evenly by dry method to prepare a mixture.

[0105] Fiberization treatment: The mixture is fiberized by air jet milling to prepare a fiberized mixture.

[0106] Preparation of positive electrode film: The fibrous mixture is rolled into a positive electrode film by rolling process.

[0107] Preparation of positive electrode sheet: The positive electrode film is rolled and laminated with aluminum foil to prepare the positive electrode sheet.

[0108] Lithium-ion battery preparation: Lithium cobalt oxide positive electrode, graphite negative electrode and PP / PE composite separator are wound and stacked to form a cell, electrolyte is injected into the cell, and lithium-ion battery is prepared by vacuum sealing, standing, formation and other processes.

[0109] The relevant parameters of Examples 1-4 and Comparative Example 1 are summarized in Table 1.

[0110] Table 1

[0111]

[0112]

[0113] Performance testing experiment

[0114] 1. Tensile strength test

[0115] Tensile strength refers to the ratio of the maximum tensile force a sample can withstand during a tensile test to the cross-sectional area. Tensile strength tests were performed on the electrodes in Examples 1-4 and Comparative Example 1, specifically according to the provisions of GB / T1040.3-2006. The test results are shown in Table 2 below:

[0116] Table 2

[0117]

[0118] 2. Cyclic capacity retention performance test

[0119] The cycle capacity retention performance of the lithium-ion batteries prepared in Examples 1-4 and Comparative Example 1 was tested.

[0120] a. Charge at 1C or the specified current to the termination voltage at room temperature, cut off current 0.05C, and let stand for 30 minutes;

[0121] b. Discharge at 1C until the final discharge voltage, record the discharge capacity, and let stand for 30 minutes;

[0122] Cyclic cycles a and b were performed, and the cyclic capacity retention was tested after 100 cycles at room temperature. The test results are shown in Table 3 below.

[0123] Table 3

[0124] Example 1 89 Example 2 91 Example 3 88 Example 4 87 Comparative Example 1 82

[0125] Performance test results show that, compared with traditional "non-composite positive electrode" and "non-composite negative electrode", the "composite positive electrode" and "composite negative electrode" prepared by the preparation method provided in this application have no cracks on the electrode surface and no breakage phenomenon. The tensile strength at break is also improved. At the same time, the lithium-ion battery prepared by the preparation method provided in this application maintains a good cycle capacity retention rate and exhibits excellent mechanical and electrochemical performance.

[0126] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0127] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A lithium-ion battery, comprising a positive electrode, a separator, a negative electrode, and an electrolyte, wherein the positive electrode comprises a positive electrode active material layer and a positive electrode current collector, and the negative electrode comprises a negative electrode active material layer and a negative electrode current collector, characterized in that, The positive electrode active material layer and / or the negative electrode active material layer form a porous fiber membrane on the side away from the positive / negative electrode current collector, and the electrolyte is dispersed in the porous fiber membrane to form a continuous lithium-ion channel; the positive electrode active material layer and / or the negative electrode active material layer comprises a fiberized mixture, which includes positive / negative electrode active materials, conductive agents and binders; the thickness of the porous fiber membrane is 10μm-12μm.

2. The lithium-ion battery according to claim 1, characterized in that, The fiberization process includes any one or a combination of two of the following: air jet milling, high-speed mixing, mechanical fusion, or twin-screw extrusion.

3. The lithium-ion battery according to claim 1, characterized in that, The porous fiber membrane is made of one or more of the following materials: polymer materials, carbon materials, metal materials, and ceramic materials.

4. The lithium-ion battery according to claim 3, characterized in that, The porous fiber membrane is made of one or more of the following materials: polyvinylidene fluoride, polymethyl methacrylate, polyimide, polyetherimide, polycarbonate, polyaramid, cellulose, polyetheretherketone, and perfluorosulfonate ether.

5. The lithium-ion battery according to any one of claims 1 to 3, characterized in that, The positive electrode active material includes LiCoO2, LiMnO2, LiNiO2, LiVO2, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiMn2O4, LiTi5O 12 Li(Ni) 0.5 Mn 1.5 The anode active material includes one or more of the following: O4, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, and LiNbO3; the anode active material includes one or more of the following: graphite, silicon, silicon-graphene, silicon-aluminum alloy, tin-based materials, graphene, pitch carbon microspheres, activated carbon, carbon fiber, and carbon nanotubes.

6. A method for preparing a lithium-ion battery, characterized in that, Includes the following steps: (1) Dry mixing of positive / negative electrode active materials, conductive agent and binder to prepare positive / negative electrode mixture; (2) The positive and / or negative electrode mixture is subjected to fibrous treatment to prepare a fibrous positive and / or negative electrode mixture; (3) Roll pressing is performed on the positive and / or negative electrode fiberized mixture to prepare a positive and / or negative electrode active material layer; (4) By rolling, a porous fiber membrane is composited on one side surface of the positive and / or negative electrode active material layer to prepare a composite positive and / or composite negative electrode membrane. (5) By rolling, the side surface of the composite positive and / or negative electrode film that is not combined with the porous fiber membrane is combined with the current collector to prepare a composite positive and / or composite negative electrode sheet. (6) A battery cell is formed by winding / stacking a composite positive electrode, a composite negative electrode, and a separator; or a battery cell is formed by winding / stacking a composite positive electrode, a non-composite negative electrode, and a separator; or a battery cell is formed by winding / stacking a non-composite positive electrode, a composite negative electrode, and a separator; an electrolyte is injected into the battery cell, and after vacuum sealing, standing, and formation processes, a lithium-ion battery is obtained. The thickness of the porous fiber membrane is 10μm-12μm.

Citation Information

Patent Citations

  • Electrode, secondary battery using same, and method for manufacturing electrode

    CN109792035A

  • Electrode assembly, method for producing same, and secondary battery including same

    CN110326152A